Screening of HPV and its genotypes in infected women Genital pests in Dhe-Qar city - Dr.Rostam Alizadeh; Alaa Aodhaib Lahmood; Amjad Hamid Rasool; Ali Raheem Abbood; Muna Ridha hussen (Genius Journals, 2023)
The current study is an analytical descriptive study in which the genital lesions of fifty women were referred to. The clinics of Dhe- Qar city from February 2021 to February 2022 took samples and sent them to the molecular department of the laboratory. They were screened using the PCR method for the presence of HPV and identified four genotypes 18, 16 (high risk) and 11, 6 (low risk). Developed at the same time as preparing a sample of patients by completing a pre-prepared questionnaire, demographic information and risk information Invoices have been recorded. The data was analyzed by spss program and descriptive statistics were used to verify the relationship between risk factors The Fisher test was used for HPV infection.
Keywords: human papilloma virus; genotype; genital lesions; polymerase chain reaction